Atherosclerotic Conditions Promote the Packaging of Functional MicroRNA-92a-3p Into Endothelial Microvesicles. Issue 4 (15th February 2019) - Liu, Yangyang; Li, Qian; Hosen, Mohammed Rabiul; Zietzer, Andreas; Flender, Anna; Levermann, Paula; Schmitz, Theresa; Frühwald, Daniel; Goody, Philip; Nickenig, Georg; Werner, Nikos; Jansen, Felix
Abstract : Rationale: : Microvesicle-incorporated microRNAs (miRs) are biomarkers and effectors of cardiovascular disease. Whether microvesicle-miR expression is regulated in coronary artery disease (CAD) or not is unknown. Objective: : Here, we explore the expression of circulating microvesicle-miRs in patients with CAD and investigate the role of microvesicle-miR in endothelial cells. Methods and Results: : Circulating microvesicles were isolated from patients' plasma by using ultracentrifugation. Electron microscopy was used to determine the size of the microvesicles. A Taqman miR array revealed certain microvesicle-miRs are significantly regulated in patients with stable CAD compared with patients with ACS. To validate the miR array results, 180 patients with angiographically excluded CAD (n=41), stable CAD (n=77), and acute coronary syndrome (n=62) were prospectively studied. Nine miRs involved in regulation of vascular performance—miR-126-3p, miR-222-3p, miR-let-7d-5p, miR-21-5p, miR-26a-5p, miR-92a-3p, miR-139-5p, miR-30b-5p, and miR-199a-5p—were quantified in circulating microvesicles by real-time polymerase chain reaction (PCR). Among these, miR-92a-3p was significantly increased in patients with CAD compared with non-CAD patients. Microvesicle-sorting experiments showed endothelial cells (ECs) were the major cell source for microvesicles containing miR-92a-3p. In vitro oxLDL (oxidized low-density lipoprotein) and IL-6 (interleukin-6) stimulation increased miR-92a-3p expression in parent ECs and upregulated the expression level of endothelial microvesicle (EMV)-incorporated miR-92a-3p. Labeling of miR-92a-3p and EMVs demonstrated that functional miR-92a-3p was transported into recipient ECs, which accelerated cell migration and proliferation. Knockdown of miR-92a-3p in EMVs abrogated EMV-mediated effects on EC migration, proliferation, and blocked vascular network formation in a matrigel plug. Polymerase chain reaction–based gene profiling showed that the expression of THBS1 (thrombospondin 1) protein—a target of miR-92a-3p and an inhibitor of angiogenesis—was significantly reduced in ECs by EMVs. Knockdown of miR-92a-3p in EMVs abrogated EMV-mediated inhibition of the THBS1 gene and protein expression. Conclusions: : Atherosclerotic conditions promote the packaging of endothelial miR-92a-3p into EMVs. EMV-mediated transfer of functional miR-92a-3p regulates angiogenesis in recipient ECs by a THBS1-dependent mechanism. Abstract : Supplemental Digital Content is available in the text.